Transformation through Infrastructure : World Bank Group Infrastructure Strategy Update FY2012-2015 - World Bank (Washington, DC, 2017)
Infrastructure can be an agent of change in addressing the most systemic development challenges of today s world from social stability to rapid urbanization, climate change adaptation and mitigation, natural disasters, and global issues such as food and energy security. Transformation through Infrastructure the updated World Bank Group Infrastructure Strategy FY12-15 - lays out the framework for transforming the Bank Group s engagement in infrastructure. It looks at the nexus between sectors and call for infrastructure to accelerate growth and even shift clients towards a more sustainable development trajectory. It also supports a new vision of who will finance infrastructure solutions. The new strategy rests on three pillars: 1) The Group will continue to do what it does well-sector based projects in support of the access and growth agenda. This will continue to represent the core of the group's engagement in infrastructure; 2) the group will support client demand for addressing the more complex, second-generation infrastructure issues. The capacity of the group to respond to these issues will require transforming how the group engages with clients and partners-by broadening the range of interlocutors interested in contributing to the solution, including middle-income countries, traditional and non-traditional donors, responsible businesses and local actors; brokering knowledge; using international for a to advance on certain global issues; collaborating more effectively with other multilateral development banks (MDBs) on issues and projects of regional or global relevance; helping align bilateral resources in order to access funding at scale; and delivering transformational projects; and 3) the Group will leverage its capital by bringing more private sector financing into infrastructure. The International Finance Corporation (IFC) will ramp up its infrastructure business, with particular attention to third party resource mobilization, Multilateral Investment Guarantee Agency (MIGA) will scale up its guarantee support and the Bank will reinforce its upstream work on the enabling environment in order to attract the private sector.